2018
DOI: 10.1096/fasebj.2018.32.1_supplement.lb224
|View full text |Cite
|
Sign up to set email alerts
|

Hemolymph Glucose Levels as a Measure of Crayfish Stress: A Methodology Using a Human Glucometer

Abstract: The objective of this study was to develop a methodology for measuring hemolymph glucose levels in crayfish of the genus Orconectes using a human glucometer. A secondary objective was to confirm through the use of this methodology that subjecting crayfish to acute stress in the form of a short‐term exposure to a basic solution or to chronic stress in the form of prolonged exposure to a nitrate‐containing solution, would increase hemolymph glucose levels. To measure the effects of acute exposure to a basic solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the present study, we also demonstrated that high temperatures markedly decreased EP fluid protein concentrations in oysters. Since the EP fluid protein binds to Ca 2+ and may act as a precursor of the soluble organic matrix in the shell [131] , a reduction of EP fluid protein concentrations may inhibit the growth and development of oysters. Moreover, the biomolecular components of EP fluid are involved in shell formation [132] , defense, and regulatory processes [75] ; therefore, an increase or decrease in any of its components may negatively affect the physiological functions and cellular integrity (i.e., DNA lesions) in oysters during heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we also demonstrated that high temperatures markedly decreased EP fluid protein concentrations in oysters. Since the EP fluid protein binds to Ca 2+ and may act as a precursor of the soluble organic matrix in the shell [131] , a reduction of EP fluid protein concentrations may inhibit the growth and development of oysters. Moreover, the biomolecular components of EP fluid are involved in shell formation [132] , defense, and regulatory processes [75] ; therefore, an increase or decrease in any of its components may negatively affect the physiological functions and cellular integrity (i.e., DNA lesions) in oysters during heat stress.…”
Section: Discussionmentioning
confidence: 99%